Transforming growth factor beta 1 expression and inflammatory cells in tooth extraction socket after X-ray irradiation - Ramadhan Hardani Putra; Eha Renwi Astuti; Rini Devijanti Ridwan (Universitas Airlangga, 2016)
Background: Radiographic examination is often used in dentistry to evaluate tooth extraction complications. X-ray used in radiographic examination, however, has negative effects, including damage to DNA and inflammatory response during wound healing process. Purpose: This study aimed to analyze the effects of X-ray irradiation on transforming growth factor beta 1 (TGF-ß1) expression and number of inflammatory cells in tooth extraction sockets. Method: Thirty rats were divided into three groups, which consist of control group (with a radiation of 0 mSv), treatment group 1 (with a radiation of 0.08 mSv), and treatment group 2 (with a radiation of 0.16 mSv). These rats in each group were sacrificed on days 3 and 5 after treatment. Inflammatory cells which were observed in this research were PMN, macrophages, and lymphocytes. Histopathological and immunohistochemical examinations were used to calculate the number of inflammatory cells and TGF-ß1 expression. Obtained data were analyzed using SPSS 16.0 software with one way ANOVA and Tukey's HSD tests. Result: There was no significant decrease in the number of PMN. On the other hand, there were significant decreases in the number of macrophages and lymphocytes in the sacrificed group on day-5 with the radiation of 0.16 mSv. Similarly, the most significant decreased expression of TGF-ß1 was found in the group sacrificed on day 5 with the radiation of 0.16 mSv. Conclusion: X-ray irradiation with 0.08 mSv and 0.16 mSv doses can decrease TGF-ß1 expression and number of inflammatory cells in tooth extraction sockets on day 3 and 5 post extraction.